Adaptation strategies for reducing vulnerability to future environmental change. Issue 8 (23rd November 2009) - Fazey, Ioan; Gamarra, Javier GP; Fischer, Joern; Reed, Mark S; Stringer, Lindsay C; Christie, Mike
Abstract : Many adaptation strategies focus on improving short‐term capacities to cope with environmental change, but ignore the possibility that they might inadvertently increase vulnerability to unforeseen changes in the future. To help develop more effective long‐term strategies, we present a conceptual framework of adaptation. The framework emphasizes that in order to ensure that existing problems are not exacerbated, adaptation must: (1) address both human‐induced and biophysical drivers of undesired ecological change; (2) maintain a diversity of future response options; and (3) nurture the kinds of human capacities that enable the uptake of those response options. These requirements are often not met when adaptation strategies rely on technological fixes, which tend to concentrate on coping with the biophysical symptoms of problems rather than addressing human behavioral causes. Furthermore, to develop effective, long‐term adaptation, greater emphasis is needed on strategies that enhance, rather than erode, the human values, skills, and behaviors conducive to sustainable activities. Participatory approaches to environmental stewardship are part of the solution to this problem.